Adverse Events due to Lack of Precision in Total Hip Arthroplasty: The Potential of Provocation-Based CT for Diagnosis of Implant Loosening - Olof Sandberg; Henrik Olivecrona; Pelle Gustafson (The Scientific World Journal)
Adverse events in total hip replacement (THR) may have several origins, one being lack of precision in diagnosis and/or during surgery. This study describes the pattern and frequency of avoidable injuries in THR and the potential value of a new tool for early diagnosis of implant loosening. This retrospective study was based on all (n = 1 456) settled claims regarding THR in the Swedish National Patient Insurance database from 2010 to 2017. The claims and medical records were analyzed for root causes, with special focus on adverse events where lack of precision could be the cause. In a second stage, we assessed in 10 patients (20 implants) the diagnostic precision of a new software tool based on provocation-CT. These were all patients where the implant loosening diagnosis was deemed as inconclusive after a first plain X-ray. The findings from the provocation-CT and plain X-ray were compared to the surgical findings at revision. While 3 of 20 implants were correctly diagnosed with plain X-ray, for dynamic CT, this number was 14 of 20 implants. The retrospective study showed that the most common types of injuries were infections (34%), nerve injury (29%), mechanical problems (14.5%), dislocation (6%), and miscellaneous complications (16.5%). Of the patients with mechanical complications, one-third had aseptic implant loosening. Statement of clinical significance: we estimated that almost 200 patients in our registry study had mechanical complications after THR, mainly implant loosening. A third of these could potentially have been diagnosed and treated if CT examination with a dedicated image analysis tool to assess implant loosening after THR had been available.